Analysis intelligent quotient with handball game performance: Study case of athletes POPDA Bandung City - Gatarina Nurani Oktavia; Agus Rusdiana; Iwa Ikhwan Hidayat; Tono Haryono; Badruzaman Badruzaman; Tian Kurniawan; Iman Imanudin (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
Sports achievement is influenced by many factors, such as physical condition, technique, tactics, and psychology. An athlete's Intellectual Ability/intelligence quotient (IQ) influences playing performance in a match. The research aims to determine the level of relationship between IQ and performance ability in playing handball. This research uses a quantitative approach using correlative descriptive methods. The sample in this study used a purposive sampling technique which resulted in 40 subjects with an age range of 16-18 years with std ± 7.178. Using two research instruments, namely collecting data for intellectual intelligence results in collaboration with psychological practitioners and using Game Performance Assessment Instrument (GPAI) analysis for handball games. Data analysis was processed using SPSS version 26 software, using the MANOVA method. Multivariate research results (p0.05) show that each component of the handball game includes decision-making (0.9280.05), skill execution (0.0820.05), support (0.8920.05), guard (0.327 0.05), and game performance (0.2070.05). Therefore, there is no significant relationship between intellectual intelligence and playing handball, but there is a positive average result of the highest relationship between intellectual intelligence and execution skills. From the findings, the game of handball must improve the execution skill/technical skill component.